Fossil Diatoms Reveal Natural and Anthropogenic History of Jackson Lake (Wyoming, USA) - John Dilworth; Jeffery R. Stone; Kevin M. Yeager; J. Ryan Thigpen; Michael M. McGlue (Earth Science, Systems and Society)
Jackson Lake supplies valuable cultural and provisioning ecosystem services to the Upper Snake River watershed in Wyoming and Idaho (western USA). Construction of Jackson Lake Dam in the early 20th century raised lake level by ∼12 m, generating an important water resource supporting agriculture and ranching, as well as tourism associated with Grand Teton National Park. Outlet engineering drastically altered Jackson Lake’s surface area, morphology, and relationship with the inflowing Snake River, yet the consequences for nutrient dynamics and algae in the lake are unknown. Here, we report the results of a retrospective environmental assessment completed for Jackson Lake using a paleolimnological approach. Paleoecological (diatoms) and geochemical datasets were developed on a well-dated sediment core and compared with available hydroclimate data from the region, to assess patterns of limnological change. The core spans the termination of the Little Ice Age and extends to the present day (∼1654–2019 CE). Diatom assemblages prior to dam installation are characterized by high relative abundances of plankton that thrive under low nutrient availability, most likely resulting from prolonged seasonal ice cover and perhaps a single, short episode of deep convective mixing. Following dam construction, diatom assemblages shifted to planktic species that favor more nutrient-rich waters. Elemental abundances of sedimentary nitrogen and phosphorous support the interpretation that dam installation resulted in a more mesotrophic state in Jackson Lake after ∼1916 CE. The data are consistent with enhanced nutrient loading associated with dam emplacement, which inundated deltaic wetlands and nearshore vegetation, and perhaps increased water residence times. The results of the study highlight the sensitivity of algal composition and productivity to changes in nutrient status that accompany outlet engineering of natural lakes by humans and have implications for water resource management.